2019
DOI: 10.1177/0730888419826622
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Exchange and Nurses’ Musculoskeletal Injuries in a Team Context: Anger as a Mediator

Abstract: Work-based musculoskeletal disorders (MSDs) are prevalent among health-care workers, particularly the nursing staff. The authors focused on the perceived social support exchange imbalance or the combination of higher perceived obligation to provide support to and lower perceived available support from the coworkers and examined the association between support exchange imbalance and nurses’ MSDs via anger. Using a sample of 410 nurses from 29 units across two hospitals, the authors found that when individual nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 61 publications
(89 reference statements)
0
21
0
Order By: Relevance
“…In a recent study of a community hospice care program, DiCicco-Bloom and DiCicco-Bloom (2019) found that when leaders support discussing and processing emotional labor in interdisciplinary meetings, it improves both care quality as well as employee experience of the care they deliver and the emotional labor in which they engage. Chang et al (2020) and Kossek et al (2019) similarly demonstrate the importance of organizational and managerial support to employee emotional experience, highlighting the importance of balance and adaptability.…”
Section: Whole Person Organizational and Social Supportsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study of a community hospice care program, DiCicco-Bloom and DiCicco-Bloom (2019) found that when leaders support discussing and processing emotional labor in interdisciplinary meetings, it improves both care quality as well as employee experience of the care they deliver and the emotional labor in which they engage. Chang et al (2020) and Kossek et al (2019) similarly demonstrate the importance of organizational and managerial support to employee emotional experience, highlighting the importance of balance and adaptability.…”
Section: Whole Person Organizational and Social Supportsmentioning
confidence: 99%
“…The papers in the special issue offer a sophisticated rendering of emotional experience and its consequences. Specifically, they depict emotion as embodied (Chang et al, 2020;Cottingham & Erickson, 2019), complex (Cottingham & Erickson, 2019), and nonobviously consequential (Lee et al, 2019). They also point toward conditions under which emotions become shared and collective (Cottingham & Erickson, 2019;Lee et al, 2020).…”
Section: The Complexity and Consequences Of Emotional Experience In Cmentioning
confidence: 99%
See 1 more Smart Citation
“…well. It was evident that, when nurses face an imbalance between the level of needed and actual social support, anxiety and anger can develop, and that can be predictive of musculoskeletal disabilities (Chang et al, 2019). The absence of family support associated with long working hours and night shifts can realistically lead to ignoring personal safety precautions.…”
Section: Social Capital Support Framework For Prevenɵon Of Occupaɵonamentioning
confidence: 99%
“…According to effort-reward imbalance model, when nurses have to fulfil the job demands with a low level of support, it creates an imbalance between these two indicators (Siegrist, 1996). This imbalance increases pressure and anger, which in turn develops the chance for safety negligence (Chang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%